Barriers to Continuing Medical Education Among Doctors in Tertiary Care Hospitals of Pakistan: a Descriptive Cross-Sectional Study - Ahmed, Amna; Abbas, Mehwish; Khurshid, Saba (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the barriers to Continuing Medical Education (CME) among doctors in tertiary care hospitals of Pakistan. Study Design: Cross-sectional study. Place and Duration of Study: Public and private tertiary care hospitals of Rawalpindi and Islamabad, Pakistan, from Feb 2025 to Apr 2025. Methodology: This study was conducted on doctors working in tertiary care hospitals of Rawalpindi and Islamabad using a structured, self-administered questionnaire. A total of 417 responses were collected through online and paper-based surveys. Results: Out of 417 respondents, only 43.2% had attended a CME activity in the past year. The primary barriers identified were lack of time due to heavy workload (63%), high cost of participation (34%), and limited local access to CME programs (26%). To address time constraints, the most preferred solution was integrating CME into work hours (42.9%), followed by shorter or flexible sessions (29%) and online programs (25.4%). For financial barriers, employer-sponsored programs (33.3%), lower registration fees (27.6%), and free online options (27.3%) were the top recommendations. Workshops and hands-on training were the most favored CME formats (59%), and opinions on mandatory CME for license renewal were nearly evenly split. Conclusion: CME participation among doctors is hindered primarily by time and financial constraints. Institutional support through work-integrated CME, financial assistance, and flexible delivery formats can significantly enhance participation. Policy-level interventions are needed to ensure equitable access and sustained professional development.